11x-6=3(7x-12)

Simple and best practice solution for 11x-6=3(7x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-6=3(7x-12) equation:



11x-6=3(7x-12)
We move all terms to the left:
11x-6-(3(7x-12))=0
We calculate terms in parentheses: -(3(7x-12)), so:
3(7x-12)
We multiply parentheses
21x-36
Back to the equation:
-(21x-36)
We get rid of parentheses
11x-21x+36-6=0
We add all the numbers together, and all the variables
-10x+30=0
We move all terms containing x to the left, all other terms to the right
-10x=-30
x=-30/-10
x=+3

See similar equations:

| 7v=6v-16 | | 0=x^2+2x-440 | | -4w=6-5w | | x+4x+6x=180 | | 10-5c+10=-10-8c | | 3(x-3)=4x+47 | | 25x+20=15x+25 | | -13t+13=-13-19t-20 | | 2(3x+5)+1=(-4x+5)+(7x-8) | | 15=02z;z | | 7(3a+2)= | | 19.24+11r=-16.3+8.2r | | x/5.9=3.5/3.2 | | 2/x+3-3/x-3=12/x^2-9 | | -19-6u=11+4u | | 18=6×y | | 58x=145 | | 8+20k=-8k-20 | | -5.3=n+4.6 | | 7/142=x | | 5x-x=x+16-x.X= | | 3(-x-4)=-3 | | -710x+14=-21 | | 5^0.9x=358 | | 3/4x=5-13 | | 12.75+13.24+5.1f=3.2f-7.45 | | 3(2a+3)-4(3a-6)=16 | | 23(x-3)=13 | | 9(3^x)-1=0 | | -3q+12+17=q-19 | | 5x-x=x+16-x÷4 | | 2(x=6)=4 |

Equations solver categories